Facies Associations of Early Cretaceous Arumit Formation and Early to Late Cretaceous Ungar Formation in Vulmali and Ungar Islands, Tanimbar (Indonesia) - Fakhruddin, Rakhmat (Indonesian Journal on Geoscience, 2019)
DOI:10.17014/ijog.6.2.185-208Cretaceous sediments are among the important petroleum system elements for hydrocarbon exploration in Tanimbar area. However, little is known about their facies associations and depositional environments. Facies association analyses have been carried out in fourteen surface sections. Early Cretaceous Arumit Formation comprises three facies associations: subtidal, intertidal, and supratidal deposits. A progradational open-coast tidal flat depositional environment suggests the deposition of sediments of the Arumit Formation. The presence of tidal rhythmites, mud drapes, and fluid mud in those sediments are diagnostic features of a tide domination process in deposition of this unit. Early to Late Cretaceous Ungar Formation in the studied area consists of four facies associations: intertidal, marine offshore to lower shoreface, upper shoreface, and foreshore deposits. An open-coast wave dominated depositional environment is proposed for deposition of sediments of the Ungar Formation. Wave dominated environments in the coarsening upward interval is represented by hummocky cross stratification, cross-bedded sand and gravel, planar parallel stratification, and low-angle stratified beds.